Escritos sobre teoría constitucional y teoría o filosofía del derecho - Castilla Colquehuanca, Jhoni Shang (Facultad de Ciencias Jurídicas y Políticas - Universidad Nacional del Altiplano de Puno, 2023)
The book that is presented brings together five papers on topics of constitutional theory and legal theory, writings that affect topics that are very much in vogue, not only in theory but also in legal practice.